The predictive value of admission blood glucose to serum albumin ratio for futile recanalization after successful interventional recanalization in acute cerebral infarction with large vessel occlusion - Zhang, Wensheng; Li, Jie; Zhou, Hongxing; Xing, Weifang; Li, Kaifeng; Li, Yudi; He, Jinzhao; He, Xiongjun; Liu, Yajie; Ling, Li (Frontiers in Neurology, 2024)
AimsWe aim to explore the predictive value of admission blood glucose to serum albumin ratio (AAR) for futile recanalization after successful interventional recanalization of acute cerebral infarction.MethodsWe retrospectively collected the data of patients suffered from acute cerebral infarction due to anterior circulation large vessel occlusion and received successful interventional recanalization from January 2019 to November 2023. Statistical analysis of clinical data was conducted using SPSS 26.0.ResultsA total of 452 patients were included in the study. There were statistically significant differences in mRS score and futile recanalization rates among the three groups of patients at 3 months after surgery according to AAR tertile. In the multiple logistic regression analysis, there were statistically significant differences in Diabetes, grade of NIHSS score at admission, AAR tertiles, good collateral circulation and Pathogenesis. The Receiver Operating Characteristic curve (ROC) curve of AAR predicting futile recanalization was drawn with an AUC of 0.582 and a 95% confidence interval of 0.529–0.634. After combining grade of NIHSS score at admission, AAR tertiles and good collateral circulation, a ROC curve was drawn to predict futile recanalization, with an AUC of 0.907 and a 95% confidence interval of 0.879–0.936.ConclusionAAR is a new composite indicator for predicting futile recanalization in patients with acute cerebral infarction with anterior circulation large vessel occlusion. The combination of grade of NIHSS score at admission, AAR tertiles and good collateral circulation has a high predictive power for futile recanalization.